Analysis of VAT Rate Increase: Social Justice and Strengthening Sustainable Economic Growth - Silalahi, Heriantonius; Kurnia, Budi (Inovasi Analisis Data, 2025)
Purpose: This study analyzes the effects of the gradual increasing of Value Added Tax (VAT) rate in Indonesia on fiscal space, household consumption, and the usage of VAT revenue for some social welfare programs. Set against a backdrop of increasing economic difficulty, the research examines how tax reforms can both enhance government revenue, while also protecting public health supported by ongoing government investment, especially among low-income households. Method: This study uses regression analyses to evaluate the impact of increased VAT rates and the tax-to-GDP ratio on household consumption and the effectiveness of VAT exemptions on essential goods. Findings: The results show that the gradual implementation of the VAT was beneficial for the tax to GDP ratio. It led to a significant increase in fiscal capacity with negligible crowding out of households. Tariff suspensions on essential goods have been instrumental in the preservation of public purchasing power, especially for low-income families. The promotion of transparency in the allocation of VAT revenues also had a positive impact on public confidence, especially in the case of social programs such as food aid and energy subsidies. Novelty: This research adopts a novel perspective of gradual VAT rises in developing economies and assesses not just the fiscal impact but also the equity dimensions and public perception aspects. The findings suggest the need to couple tax reforms with specific incentives to help protect vulnerable populations when taxes do go up. Implications: The findings of the study provide important insights for policymakers aiming for a balance between fiscal sustainability and social protection. It highlights the importance of transparent allocation of tax revenues, efficient administration of taxes, and digital infrastructure in enhancing compliance. These observations can be a guide for other developing countries looking to undertake similar VAT reforms to ensure both economic progress and social justice.